How commercial publishers play a role in developing a sustainable model for Open Access publishing - Ryste, Marte Ericsson; Stieglitz, Katia; Aase, Simon (Septentrio Conference Series, 2017)
One of the objectives of the open access movement has been to upend the traditional model for scholarly publishing by making research findings freely available to anyone, anywhere. The trend emerged partly in response to the major publishing houses having become the gatekeepers of the dissemination of research findings and setting high prices for access to this material via subscriptions to scholarly journals. On the face of it, this state of affairs suggests that commercial actors have no place in the realm of open access publishing. However, an argument can be made to the effect that commercial companies have a part to play in transforming the way scientific publication works and contribute to making research freely available. Having numerous interested parties in the OA domain may contribute towards making research accessible, leading to a general increase in innovation. This is necessary in a field that by and large is in its infancy, technologically, politically and economically. An OA initiative that is part of a profit-driven organization does not preclude it from contributing to a sustainable publishing model, and a commercial approach is not necessarily incompatible with the principles. In this poster we offer NOASP as an example, and part of the wider context of commercial open access publishing. Nordic Open Access Scholarly Publishing is an open access publisher of scholarly journals and books in Scandinavia and a subdivision of Cappelen Damm Akademisk. NOASP was established in 2015 – and continues to grow. In our experience, meeting the very specific criteria for Open Access publishing requires substantial investments in technology and human resources. Publishers who choose to establish themselves in this niche area must have a long-term strategy and develop specific expertise. Competition between publishing houses and other actors provides incentives for staying abreast of new requirements and standards, technology and infrastructure. These strategic and economic factors directly and positively impact the quality of journals and publishing solutions, and ultimately contribute to innovation in the field. The economics of commercial publishing, by heightening competition between the services publishers provide, therefore leads to improvement of both technical platforms and editorial practices. In turn, this leads to higher quality of the end product and broader distribution of the freely available research, which should ultimately be the goal of the OA movement.